2004
DOI: 10.1364/ao.43.000592
|View full text |Cite
|
Sign up to set email alerts
|

Model of image degradation due to wind buffeting on an extremely large telescope

Abstract: A parametric model of wind buffeting on an extremely large telescope with a multipod secondary support is described. The model estimates wave-front errors that are due to wind buffeting on a segmented primary, wind-induced secondary figure and position errors, and primary-mirror deformations caused by wind forces on the secondary support. The approach is based on a Zernike expansion of pressure fluctuations, with simple models of stiffness, resonance, and control. The model shows that wind buffeting on a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…While the enclosure surrounding the telescope provides a significant reduction in wind speeds, the residual wind loads that result from large-scale flow structures and turbulence inside the enclosure may still lead to significant vibration. 1,2 Estimates of the wind loads are required early in the design process, influencing the design of the enclosure, telescope structure, and control system. The wind parameterization herein reflects our best current understanding of the wind environment inside a roughly hemispherical telescope enclosure, informed by three separate sources of data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the enclosure surrounding the telescope provides a significant reduction in wind speeds, the residual wind loads that result from large-scale flow structures and turbulence inside the enclosure may still lead to significant vibration. 1,2 Estimates of the wind loads are required early in the design process, influencing the design of the enclosure, telescope structure, and control system. The wind parameterization herein reflects our best current understanding of the wind environment inside a roughly hemispherical telescope enclosure, informed by three separate sources of data.…”
Section: Introductionmentioning
confidence: 99%
“…Although the crosssectional area of M2 is small compared to that of M1, the structure around the mirror is exposed to higher wind speeds, and thus the resulting forces are also a significant contributor to image degradation, 1 resulting in the motion of M2 and the deformation of M1 through structural coupling. Steady forces can be compensated by active control of the mirror surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Finally, computational fluid dynamics (CFD) [13][14][15] is an ideal design tool, and can take advantage of the experimental data for validation, so that CFD can be used with confidence in future design work. The parametric model of wind forces herein builds on earlier efforts 3,4 by incorporating new information from recent computational and wind tunnel studies. The structural model is not yet parameterized; future efforts will include some parameterization of the structural finite element model (FEM) node geometry by using an input file as was done with VLOT.…”
Section: -8mentioning
confidence: 99%
“…Several studies have analyzed the wind-induced buffeting of the telescope structure that results from turbulence inside the telescope enclosure [3][4][5] and concluded that this vibration must be taken into account in the design process, affecting the design of the telescope enclosure, the telescope structure and the active control system. Estimating the degradation in image quality that results from the wind-induced vibration requires understanding the wind inside the enclosure, coupling these forces to a structural model, estimating the achievable reduction in vibration using active control, and computing the optical consequences of the residual vibration.…”
mentioning
confidence: 99%
“…Padin and Davison [11] added both structural dynamic amplification and the response of M1 due to loads on the top end structure. Neither of these latter effects should be significant for a well-designed structure, although their analysis was essential to ensuring that this is true for future telescopes.…”
Section: Introductionmentioning
confidence: 99%